Deteksi dini anemia pada remaja putri di SMA Unggulan Haf-Sha Zaha - Widayati, Agustina; Narsih, Umi (P3HKI - Universitas Muhammadiyah Parepare, 2024)
Anemia is a common global health problem, especially among adolescent girls, with a higher prevalence in Indonesia. Anemia will cause a decrease in the blood's ability to bind and transport oxygen from the lungs to the rest of the body. This process occurs very quickly, so it requires high energy and protein. This requires adolescents to be able to fulfill their food needs with adequate nutritional substances. The aim of this Community Partnership Program is for young women to receive proper education about early detection of anemia, especially in adolescence. The method used is to collaborate with the SMAU Haf-Sha Zaha provides education regarding early detection of anemia in adolescent girls. The success of this program was evaluated based on increased awareness and improved practices of early anemia detection among adolescent girls, as assessed through pre-test and post-test measurements. This activity has run smoothly so that it has received good benefits starting from increasing enthusiasm for young women in practicing early detection of anemia. Many young women at SMAU Haf-Sha Zaha have received information and support from teachers and families to carry out early detection of anemia in young women independently. Young women receive education about the prevention and appropriate treatment of anemia. Anemia will cause a decrease in the blood's ability to bind and transport oxygen from the lungs to the rest of the body. If the oxygen needed is not enough, it will result in difficulty concentrating so that learning achievement decreases.